2021
DOI: 10.1016/j.clml.2021.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Homoharringtonine for the Treatment of Acute Myeloid Leukemia: A Meta-analysis

Abstract: Since the first clinical trial using homoharringtonine (HHT) was performed in China, a considerable amount of research has been conducted to provide a more scientific basis for HHT applications. We conducted a metaanalysis of 37 studies to summarize control studies reviewing the use of HHT in the treatment of acute myeloid leukemia. Background: To evaluate the efficacy and safety of homoharringtonine (HHT) in acute myeloid leukemia (AML). Methods: PubMed, Cochrane Library, Embase, China National Knowledge of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Recently, several retrospective studies from China, including our own, have consistently shown that patients with AE-AML are less likely to be responsive to VEN plus HMA therapy, regardless of ND or R/R patients [ 7 – 9 , 23 25 ]. In ND-AE-AML, Dai et al showed that the standard 7 + 3 regimen acquired a statistically higher response than the VEN plus HMA regimen, with a CR/CRi rate of 61.8% versus 37.8% ( P = 0.02) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several retrospective studies from China, including our own, have consistently shown that patients with AE-AML are less likely to be responsive to VEN plus HMA therapy, regardless of ND or R/R patients [ 7 – 9 , 23 25 ]. In ND-AE-AML, Dai et al showed that the standard 7 + 3 regimen acquired a statistically higher response than the VEN plus HMA regimen, with a CR/CRi rate of 61.8% versus 37.8% ( P = 0.02) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Currently, HHT is widely used in leukemia treatment. [ 7 ] It was shown that HHT could block protein synthesis by competing with incoming aminoacyl-tRNAs to bind to the peptidyl-transferase center. [ 8 , 9 ] In acute myeloid leukemia, HHT affects the DNA epigenome through the SP1/TET1/5hmC axis; [ 10 ] it has been reported to inhibit breast cancer cell growth via the miR-18a-3p/AKT/mTOR signaling pathway [ 11 ] and reduce MYC expression by binding directly to the nuclear factor-kappa B (NF-κB) repressing factor.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Homoharringtonine (HHT) can be a reliable choice for patients with AML, especially for newly diagnosed or patients younger than 60. Additionally, the use of HHT can reduce relapse in elderly intolerant patients ( Mi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%